Sistem Rekomendasi Untuk Penentuan Konsentrasi Pada Program Studi Informatika Universitas Muhammadiyah Surakarta Dengan Fuzzy - Fitriani, Efrina; , Yogiek IndraKurnawan, S.T., M.T (2017)
In the determination of Concentration requires a recommendation system as an alternative to taking the decision to vote with the right concentration. The problems faced by students of the Informatics courses Muhammadiyah University of Surakarta (UMS) in determining the concentration according to his own abilities and interests is very difficult, let alone with a student who is not confident with his ability, follow friends and lack of information known by students about the concentration there is. Therefore, the recommendation system built in this study as one of the alternative attempts to address these problems. Determination of the concentration of established based on several criteria/consideration which has been determined, that interest student (using questionnaires/ question form) and the value of the course (transcriptions) in each concentration. Implementation using matlab and the research method using fuzzy mamdani. Mamdani's method is a method of study that corresponds to such research, because using the operation of min-max. In mamdani method there are aeveral stage of calculations to provide output in the form of recommendations and the results of the comparison of the student in question. The results of this research in the form of a recommendation system that helps students to determine the concentration of the desired criteria and based on the results of the accuracy rate of 98 .102 of the data.